Morphology controlled NiCo2O4 as anode materials for high electrochemical performance lithium‐ion batteries. Issue 1 (24th August 2020) - Huo, Jiaofei; Zhang, Guangpeng; Wang, Yinwei
Abstract: BACKGROUND: Due to the high energy density of lithium‐ion batteries, they have become the main power sources for electric vehicles. However, lithium‐ion batteries suffer from severe capacity fading during their electrochemical cycles. Therefore, it is significant to develop perfect electrode materials for lithium‐ion batteries. It is known that the traditional anode materials have low specific capacity value and poor cycle performance. To overcome this problem, a novel anode material is designed in our work. RESULTS: In electrochemical tests, the initial specific capacity of the NiCo2 O4 spheres/nanosheets (NCOs/n) electrode is as high as 1426 mAh g −1 at the current density of 0.2 C. The capacity of the NCOs/n electrode can maintain at 1020 mAh g −1 at the current density of 1C after 1000 cycles. CONCLUSIONS: The as‐prepared NCOs/n electrodes exhibit high specific capacity value and superior cycle stability in high current densities. © 2020 Society of Chemical Industry